Species circumscription within the Rediviva neliana group (Hymenoptera: Melittidae), with the description of the new species Rediviva vogeli sp. nov. Melin & Colville - Melin, Annalie; Manning, John C.; Colville, Jonathan F. (Zootaxa, 2024)
Rediviva neliana Cockerell 1931 has been considered to be widely distributed along the southeastern and eastern Escarpment of South Africa and Lesotho, with high variation in foreleg length recorded across populations. A recent analysis of the allometric relationship between foreleg length and body size for the oil-collecting species of Rediviva revealed that R. neliana is a notable ‘outlier’, suggesting that it represented a group of species and not a single taxon. This hypothesis necessitates a critical review of the taxonomy of R. neliana. Here, we examined a large amount of old (n = 1228) material as well as more recent material collected from 23 different sites across the Great Escarpment, including the resurveying of type localities. Based on this, we (i) redescribe the male of R. neliana and the previously unknown female; (ii) reinstate R. politissima (Cockerell 1934) stat. rev. from synonymy with R. neliana, and redescribe both the male and female; (iii) reassign the male of R. whiteheadi Kuhlmann 2012 to R. autumnalis Whitehead & Steiner 2008, and include the female of R. whiteheadi syn. nov. into synonymy with R. neliana; (iv) reassign 242 specimens of R. neliana to R. steineri Kuhlmann 2012, thus vastly expanding the known distribution of the latter taxon; (v) describe both sexes of the new species R. vogeli Melin & Colville sp. nov.; and (vi) provide a revised key to the species of Rediviva occurring in the southern African summer-rainfall region based on the shape of the galea and male genitalia. Detailed images of genitalia and hidden sterna are also provided for all species of Rediviva in the summer-rainfall region for which males are known. We conclude that the R. neliana group comprises four species. Understanding their geographic distributions is relevant to assessing their conservation status and understanding their coevolution with host plants.